2004
DOI: 10.1203/01.pdr.0000100901.88697.66
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin II Receptor Blockade Inhibits Pneumocyte Apoptosis in Experimental Meconium Aspiration

Abstract: Lung tissue inflammation and apoptosis are implicated in the pathogenesis of meconium aspiration-induced lung injury in the newborn, but the mechanisms of these reactions are still poorly known. We investigated the time-dependent leukocyte influx and appearance of apoptosis, as well as the contribution of angiotensin (ANG) II receptor action on these processes in the meconium-induced lung injury. Experimental meconium aspiration was induced by intratracheal instillation of human meconium in 18 rats, and eight … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
34
0

Year Published

2005
2005
2010
2010

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 40 publications
(54 reference statements)
5
34
0
Order By: Relevance
“…In a similar study of rats, Lukkarinen et al 69 showed that pretreatement of rats with the nonselective ANG receptor blocker saralasin, given intraperitoneally before meconium instillation, prevented AEC apoptosis detected by both DNA fragmentation assay and electron microscopy. The meconium increase AGT mRNA in the lungs, suggesting apoptosis-induced upregulation of AGT in AECs.…”
Section: The Endocrine Ras Versus Local Tissue Rasesmentioning
confidence: 93%
“…In a similar study of rats, Lukkarinen et al 69 showed that pretreatement of rats with the nonselective ANG receptor blocker saralasin, given intraperitoneally before meconium instillation, prevented AEC apoptosis detected by both DNA fragmentation assay and electron microscopy. The meconium increase AGT mRNA in the lungs, suggesting apoptosis-induced upregulation of AGT in AECs.…”
Section: The Endocrine Ras Versus Local Tissue Rasesmentioning
confidence: 93%
“…Previous studies in our laboratory in fact demonstrate that human meconium contains high amount of PLA 2 -I and that the PLA 2 activity and concentration of PLA 2 -I in the meconium-contaminated lung tissue is high (3). Although these results connected intra-tracheal insufflation of particulate meconium with pulmonary inflammation, there are also data suggesting an important role for the soluble fraction of human meconium in the initiation of acute inflammatory response in the insulted lungs (3,4). We hypothesized that PLA 2 -I is present in both particulate and soluble fraction of meconium and that it contributes to the inflammatory and apoptotic lung injury induced by meconium aspiration, and therefore decided to investigate the pulmonary effects of meconium before and after extraction of PLA 2 -I, and also the direct effects of intra-tracheal PLA 2 -I.…”
mentioning
confidence: 89%
“…The pathophysiology of the neonatal meconium aspiration syndrome (MAS) is complex, but inflammation with pulmonary surge of cytokines, possibly through activation of alveolar macrophages, and accumulation of polymorphonuclear leukocytes in the pulmonary tissue is believed to be a central event in the development of acute tissue damage (1,2). This inflammatory reaction is connected with increased lung epithelial cell apoptosis, which may together with inactivation of the pulmonary surfactant and direct toxic effects of meconium significantly contribute to the lung injury process (1,3,4). Still, the clinical effects of anti-inflammatory therapeutic approaches are unsatisfactory and do not consistently improve the outcome of severe complications of this disease (1).…”
mentioning
confidence: 99%
“…24 In addition, meconium has been shown capable of upregulating cyclooxygenase-2 mRNA expression in rat lungs, a process that is inhibited by dexamethasone, but not indomethacin 25 and enhance the release of thromboxane-A 2 in human airway epithelial cells. 26 Finally, apoptosis associated with meconium 22,27,28 could be inhibited by angiotensin II receptor blockade. 27 The effect of meconium on oxidative burst (release of reactive oxygen species) has been difficult to interpret.…”
Section: Inflammatory Mediators In Masmentioning
confidence: 99%
“…26 Finally, apoptosis associated with meconium 22,27,28 could be inhibited by angiotensin II receptor blockade. 27 The effect of meconium on oxidative burst (release of reactive oxygen species) has been difficult to interpret. Although one study showed that meconium stimulated alveolar macrophages to produce superoxide anion, 29 another study showed that light and very light meconium inhibited neutrophil oxidative burst.…”
Section: Inflammatory Mediators In Masmentioning
confidence: 99%